Extender Combination of Date Palm Juice (Phoenix dactylifera) and Lactatic Ringer on Spermatozoa Quality of Freshwater Fish - Fani Fariedah; Maheno Sri Widodo (Journal of Aquaculture and Fish Health, 2020)
This study aims to determine the effect of the extender combination of dates and ringer lactate extracts on the quality of spermatozoa of some freshwater fish in the process of preserving spermatozoa. The process of sperm preservation depends on the nutrients provided by the extender material. Ringer lactate has been used as an extender in the process of preserving sperm which is useful as an energy provider. Other energy can be obtained from materials that contain fructose or glucose. Date palm juice is one ingredient that has a fructose and glucose content that is expected to help provide energy for sperm during the process of sperm preservation. In this study an experiment of sperm preservation of several freshwater fishes carp (Carassius auratus), Siamese catfish (Pangasius hypophthalmus), and Koi (Cyprinus carpio) using an extender made in combination from ringer lactate and date palm solution. This study used different concentrations of date extracts i.e. 0.5%, 1%, 2.5%, 2% used randomized group design with fish as group. The results showed that the average of the Siamese’s motility achieved the highest value (52,00%) while the highest average fertilization rate occurred on Carp spermatozoa with a value of 97,06%. Palm juice solution can provide nutrients to the spermatozoa during the preservation process because the juice of dates contains fructose and glucose so that preserved spermatozoa can still fertilize normally.